ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BULUKUMBA - Santuo Santuo (Jurnal Administrasi Negara, 2019)
Taxpayer compliance is influenced by several factors, including tax regulation comprehension of taxpayer, service quality of tax authorities and tax audits. This study aims to determine the effect of tax regulation comprehension of taxpayer, service quality of tax authorities and tax audits of taxpayer compliance at Bulukumba Small Tax Office. The number of samples used as respondents in this study are 100 taxpayers at Bulukumba Small Tax Office. Data collection technique used is through questionnaire. Data analysis used is through multiple linear regression analysis with partial and simultaneous hypothesis tests. The results indicate that there is a positive and significant influence on tax regulation comprehension of taxpayer, service quality of tax authorities and tax audits of taxpayer compliance. This means that taxpayer compliance at Bulukumba Small Tax Office is generally influenced by tax regulation comprehension of taxpayer, service quality of tax authorities and tax audits, and the others is influenced by other factors not included in this research model.